La Gouvernance Comme Mecanisme pour Soutenir la Croissance des Start-Ups: Cas des Startups en Algerie - Dahman, Jalel Eddine; Miloudi, Mohamed Karim (القطب الجامعي بالقليعة - مدرسة الدراسات العليا التجارية, 2020)
The pupose of this work is to try to analyze the governance structures of the startup, and to study the perception of the Algerian leader in relation to governance, first through a theoretical reading, then by a survey carried out with of a sample of many Algerian startups.
Keywords: آليات الحوكمة -- نمو الشركات -- تكنولوجيا الاتصالات -- الجزائر